Should Epidemiological Studies Be Subject to Ethics Review?. (31st October 2017) - Piasecki, Jan; Dranseika, Vilius; Waligora, Marcin
Abstract: Epidemiological studies usually do not pose high risk to participants. At the same time they provide valuable knowledge and improve public and individual health. In many countries, studies involving human subjects are subject to ethics review. Research shows that the process of obtaining ethical approval from institutional research boards or research ethics committees is sometimes costly, time-consuming and seriously delays important research projects. In this article we consider arguments against and in favor of ethics review of epidemiological studies. On the one hand, it seems that minimal risk epidemiological studies should not be a subject to ethics review, since any delay of an important study has its death toll and health costs. In this perspective, the calculus of costs and benefits supports rejecting the whole existing approach. Nevertheless, we argue that institutional research boards or ethics research committees protect research participants from wrongs and up till now are the best tools of social and political control over the research enterprise.